The Influence of Enterprise Risk Management, Slack Resources and Tax Avoidance on Firm Value (Empirical Study of Primary Consumer Sector Companies Listed on the Indonesian Stock Exchange 2020-2022) - Gustina, Salsabila Ayu; Safelia, Nela; Ridwan, Muhammad (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to investigate the impact of enterprise risk management, slack resources, and tax avoidance on the valuation of primary consumer sector companies listed on the Indonesia Stock Exchange during the period from 2020 to 2022. The research employs a quantitative approach with purposive sampling method, utilizing a sample size of 132 companies. Data analysis includes descriptive statistics and multiple linear regression analysis conducted applying Eviews version 12 software. The findings suggest that enterprise risk management has a statistically significant negative influence on firm value, whereas slack resources and tax avoidance do not significantly affect firm value.